Market structure in the Vietnamese banking system: a non-structural approach. Issue 1 (12th February 2018) - Nguyen, Thao Ngoc; Stewart, Chris; Matousek, Roman
Abstract : Purpose: This paper aims to examine the market structure of Vietnam's banking sector during 1999-2009, which is after the introduction of the two-tier banking system, using the non-structural (Panzar–Rosse) model. Design/methodology/approach: The authors consider a more comprehensive range of specifications, in terms of a greater number of environmental covariates and different dependent variables, than in the previous applications of this model. Further, this is the first study that uses lagged input prices (to avoid endogeneity), excludes assets (to avoid specification bias) and includes a lagged dependent variable (to avoid dynamic panel bias) in such a study of the Vietnamese banking system. Findings: The authors find that the Vietnamese banking system operates in monopoly. Originality/value: The main contribution of this paper is to determine the market structure in the recent period after the Vietnamese banking system was transformed into a less centralised, two-tier system. This study is the first to uniquely identify the market structure of this developing economy's banking system (using data only for Vietnam and not observations from other countries) in a post-transition period.